Lists and registers in Written and oral Tradition - Zadka, Małgorzata (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The aim of this article is to show that ancient lists, registers and catalogues, even if concerning similar issues, are differentiated depending on whether they derive from the oral or written tradition. By comparing oral and written records I aim to present the causes of the differences. Oral lists are narrative and semantically complete. Written registers are strongly contextual and consist only of necessary words. Therefore the narrativity of catalogues or registers should be treated as proof of their oral origin.
Keywords: orality; written records; lists; registers